BIDIRECTIONAL ASSOCIATION BETWEEN DEPRESSION AND DIABETES - MANASI BEHERA,; DIPTI MOHAPATRA,; NIBEDITA PRIYADARSINI,; PRIYAMBADA PANDA, (International Journal of Pharma and Bio Sciences, 2014)
Diabetes mellitus is a major health problem not only in developing countries but also in developed countries. Depression and diabetes are two major health disorders that are bidirectionally associated. Some studies show strong relationship between diabetes and depression. Sometimes diabetes and depression combinedly increase the mortality and morbidity rate. Early identification and proper treatment of depression can improve the quality of life.